Modification of honeycomb bioceramic scaffolds for bone regeneration under the condition of excessive bone resorption. Issue 6 (18th February 2019) - He, Fupo; Lu, Teliang; Fang, Xibo; Tian, Ye; Li, Yanhui; Zuo, Fei; Ye, Jiandong
Abstract: Gallium (Ga) ions have been clinically approved for treating the diseases caused by the excessive bone resorption through the systemic administration. Nevertheless, little attention has been given to the Ga‐containing biomaterials for repairing bone defects under the pathological condition of excessive bone resorption. In the current study, for the first time the Ga‐containing phosphate glasses (GPGs) were introduced to modify the honeycomb β‐tricalcium phosphate (β‐TCP) bioceramic scaffolds, which were prepared by an extrusion method. The results indicated that the scaffolds were characterized by uniform pore structure and channel‐like macropores. The addition of GPGs promoted densification of strut of scaffolds by achieving liquid‐sintering of β‐TCP, thereby tremendously increasing the compressive strength. The ions released from scaffolds pronouncedly inhibited osteoclastogenesis‐related gene expressions and multinuclearity of RAW264.7 murine monocyte cells, as well as expressions of early osteogenic makers of mouse bone mesenchymal stem cells (mBMSCs). However, the scaffolds with lower amount of Ga increased cell proliferation and upregulated expression of late osteogenic maker of mBMSCs. This study offers a novel approach to modify the bioceramic scaffolds for bone regeneration under the condition of accelerated bone resorption. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 1314–1323, 2019.